Diagnostic Accuracy of Non-Contrast Magnetic Resonance Imaging in Diagnosing Pituitary Micro-Adenoma, Taking Histopathology as Gold Standard - Sehar Sarfraz; Tayyaba Ali; Pakeeza Shafiq; Zartashia Khan; Waqar Azeem; Ghazala Rasool; Ehsan Ul Haq (Pakistan Journal of Medicine and Dentistry)
Background: Pituitary microadenomas (PMs) are common benign tumors that are often not visualized even when they are present due to their asymptomatic nature. The objective of the study was to evaluate the diagnostic accuracy of non-contrast magnetic resonance imaging (MRI) in the diagnosis of pituitary microadenomas using histopathology as a gold standard.